2020
DOI: 10.1002/btm2.10161
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles containing constrained phospholipids deliver mRNA to liver immune cells in vivo without targeting ligands

Abstract: Once inside the cytoplasm of a cell, mRNA can be used to treat disease by upregulating the expression of any gene. Lipid nanoparticles (LNPs) can deliver mRNA to hepatocytes in humans, yet systemic non-hepatocyte delivery at clinical doses remains difficult. We noted that LNPs have historically been formulated with phospholipids containing unconstrained alkyl tails. Based on evidence that constrained adamantyl groups have unique properties that can improve small molecule drug delivery, we hypothesized that a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…Using DNA barcode-labelled oligonucleotides, the distribution of different lipid nanoparticle formulations can be analysed in a high-throughput manner in vivo 121 , for example, to quantify targeted delivery of nucleic acids in multiple tissues 121 . Based on this method, a series of phosphatidylcholines containing constrained adamantyl groups has been explored for mRNA delivery, including analysis of distribution in different cell types 122 .…”
Section: Development Of Lipids For Mrna Deliverymentioning
confidence: 99%
“…Using DNA barcode-labelled oligonucleotides, the distribution of different lipid nanoparticle formulations can be analysed in a high-throughput manner in vivo 121 , for example, to quantify targeted delivery of nucleic acids in multiple tissues 121 . Based on this method, a series of phosphatidylcholines containing constrained adamantyl groups has been explored for mRNA delivery, including analysis of distribution in different cell types 122 .…”
Section: Development Of Lipids For Mrna Deliverymentioning
confidence: 99%
“…The importance of LNP composition optimization in screening carried out by Sago et al resulted in finding 7C2 and 7C3 LNPs that efficiently target endothelial cells, as previously noted [ 147 ]. Using the same screening methodology as Sago et al, Gan et al recently tested a library of 109 LNPs composed of “constrained phospholipids” that contained an adamantylhydrocarbon chain [ 154 ]. This study identified a novel LNP that delivers mRNA to Kupffer cells instead of hepatocytes, without targeting ligands [ 154 ].…”
Section: Boosting the Efficacy And Safety Of Lnp-mrna Applicationsmentioning
confidence: 99%
“…Using the same screening methodology as Sago et al, Gan et al recently tested a library of 109 LNPs composed of “constrained phospholipids” that contained an adamantylhydrocarbon chain [ 154 ]. This study identified a novel LNP that delivers mRNA to Kupffer cells instead of hepatocytes, without targeting ligands [ 154 ]. Recently, Zukancic et al used Onpattro ® LNP, where the authors replaced 1, 2-Distearoyl-sn-glycero-3-phosphoethanolamine-Poly(ethylene glycol) (PEG-DSPE) with Tween 20 containing short (C11) PEG alkyl chain [ 155 ].…”
Section: Boosting the Efficacy And Safety Of Lnp-mrna Applicationsmentioning
confidence: 99%
“…By applying a siGFP/DNA-barcoded system in transgenic eGFP mice, the group found that constrained lipid nanoparticles (cLNPs) containing a conformationally constrained adamantane tail can deliver siRNA and sgRNA to splenic T cells in vivo at low doses [ 197 ], and in contrast to standard LNPs do not preferentially target hepatocytes. Based on this, the group further demonstrated cLNP containing adamantyl phospholipids can delivery Cre mRNA to liver immune cells at low doses [ 198 ]. Like reported before [ 188 ], delivery takes place in a size-independent and chemical composition-dependent manner, providing a potential alternative for further active targeting based on chemical modification and not targeting ligands.…”
Section: Barcoding—a New Mode To Apply Sequences For Finding In VImentioning
confidence: 99%